Pendampingan Penggunaan Teknologi Tepat Guna Botol Bekas Pembasmi Nyamuk Dalam Upaya Pencegahan Penyakit Demam Berdarah Dengue (DBD) - Muhammad Kambali; Sochifa; Dicky Nur Alimin; Nova Auliyatul Faizah; Maulida Nur Chofifah (PUDAK: Local Wisdom Community Journal, 2022)
Community empowerment carried out related to efforts to prevent dengue fever by using appropriate technology aims to provide information related to the dangers of Dengue Hemorrhagic Fever and its prevention efforts carried out in Sooko village, Wringinanom sub-district, Gresik district. The research method used is the ABCD (Asset Based Community Development) method where in this method there are five stages which include: Define (Determine the Topic), Discovery (Deep Discovery), Dream (Dream), Design (Design and Design), Deliver or Destiny (Executing and Controlling). This community empowerment activity is said to be successful because it is in accordance with the objectives. The impact that can affect this activity is the reduction in the mosquito population, it can be proven by the presence of mosquito larvae that enter the mosquito exterminator. In addition, the insight gained by the community regarding the dangers of dengue hemorrhagic fever is getting wider. So that citizens can maximize in maintaining the cleanliness of the environment.